Assessing the role of fractures on the permeability of the Permo-Triassic sandstones at the Soultz-sous-Forêts (France) geothermal site. (July 2018) - Kushnir, Alexandra R.L.; Heap, Michael J.; Baud, Patrick
Highlights: Fractures increase permeability of the sandstone by up to six orders of magnitude. Fractures facilitate sustained regional hydrothermal convection. Calculated equivalent permeability is consistent with borehole hydraulic conductivity. Abstract: Quantification of the systemic permeability of geothermal reservoirs is essential to the assessment of their economic feasibility. Here we investigate experimentally the role of fractures on the permeability of a 400 m-thick unit of Permo-Triassic sandstone from the EPS-1 exploration borehole in the Upper Rhine Graben near Soultz-sous-Forêts (France). The permeability of initially intact sandstone samples was measured before and after the introduction of a through-going tensile fracture. While the permeability of the fracture-free samples varied over five orders of magnitude between 1 × 10 −19 and 1 × 10 −14  m 2, the presence of through-going fractures increased sample permeability to between 8 × 10 −14 and 4 × 10 −12  m 2 . Using the fracture aperture of open fractures provided by borehole televiewer data, we model the equivalent permeability down the borehole to be between 7 × 10 −18 and 3 × 10 −13  m 2, which is in agreement with values of hydraulic conductivity determined using borehole tests. Overall, these equivalent permeability values are not sufficiently high to sustain hydrothermal convection at Soultz-sous-Forêts, highlighting the need for continued anthropogenic stimulation.